Preparation method of carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode
By using carboxylated polyaniline/phosphorus doped staging pore carbon/MoS2 integrated film electrodes in MCDI electrode materials, the problems of lower capacitance and poor hydrophilicity of existing electrode materials are solved, and a more efficient low-concentration uranium-containing Desalination properties of wastewater.
Patent Information
- Application Number
- CN202310520268.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-10
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-05-10
AI Technical Summary
The existing MCDI electrode materials have low specific capacitance, poor hydrophilicity, and insufficient membrane permeability and conductivity, which affect the effect of treating low-concentration uranium-containing wastewater.
Carboxylated polyaniline/phosphorus doped graded pore carbon/MoS2 integrated film electrode is adopted to recombine with MoS2 through phosphorus doped graded pore carbon to improve the pore structure and hydrophilicity of the electrode material, and form carboxylated conductive polymerization on the electrode surface. The film improves ion exchange performance and conductivity.
The specific capacitance, hydrophilicity and selective permeability of the electrode material are significantly improved, and the desalination performance of MCDI treatment of low-concentration uranium-containing wastewater is improved.
Smart Images

Figure CN116282414B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemical separation, and in particular to a method for preparing a carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode. Background Art
[0002] A large amount of uranium-containing wastewater is produced during the nuclear fuel cycle, and the resulting radioactive pollution seriously harms the environment and human health. Membrane capacitive deionization (MCDI) is a new separation technology developed in recent years. MCDI is to place a reverse ion exchange membrane in front of the electrode, that is, to place a cation exchange membrane and an anion exchange membrane in front of the cathode and anode respectively, and use an external electric field to induce the ions in the solution to selectively pass through the ion exchange membrane and be enriched in the pores of the porous electrode (such as the carbon electrode). Through potential regulation, the ions can be quickly embedded / released in the porous electrode. MCDI ion exchange membrane can be used as an ion permeation selective barrier to improve the distribution of adsorbed ions, reduce electrode side reactions, and improve desalination performance. Using MCDI to treat low-concentration uranium-containing wastewater has the advantages of energy saving, high efficiency, simple operation, economy and environmental protection.
[0003] High-performance electrode materials and membrane materials are the key to using MCDI to treat low-concentration uranium-containing wastewater. The performance of electrode materials mainly depends on the material's specific capacitance, conductivity, hydrophilicity and membrane permeability. At present, the carbon electrode materials commonly used in MCDI are mainly microporous, with low specific capacitance and poor hydrophilicity; in addition, the ion exchange membrane used in the membrane capacitor deionization device is separated from the electrode material, and the commercially available ion exchange membrane is thicker, and the membrane permeability and conductivity are poor, which seriously affects the actual effect of MCDI in treating low-concentration uranium-containing wastewater. Therefore, how to improve the pore structure of MCDI electrode materials, increase the material's specific capacitance and hydrophilicity, and increase the membrane permeability and conductivity have become technical problems that need to be solved when using MCDI to treat low-concentration uranium-containing wastewater. Summary of the invention
[0004] The purpose of the present invention is to solve the defects of the prior art and provide a method for preparing a carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode comprises the following steps:
[0007] S1, preparation of phosphorus-doped hierarchical porous carbon;
[0008] Mesoporous carbon was synthesized by using coal tar as the carbon source and template method: 5% template F127 was added to 100 mL coal tar and mixed, and then 6 g phytic acid was added as the phosphorus source and mixed, and ultrasonicated for 30 min. The mixture was added to the reactor and stirred at 210 °C for 12 h. The product was filtered and dried to obtain the phosphorus-doped carbon precursor.
[0009] The phosphorus-doped carbon precursor prepared above was placed in the middle of a tube furnace, heated and carbonized for 2 h at 700 °C in a mixed atmosphere of N2+water vapor+CO2 in a volume ratio of 1:1:1, and the template F127 was removed simultaneously. The obtained carbonized product was washed with water and vacuum dried to obtain phosphorus-doped hierarchical porous carbon;
[0010] S2, preparation of phosphorus-doped hierarchical porous carbon / MoS2;
[0011] First, 18.6 g of ammonium molybdate and 34.2 g of thiourea were dissolved in 1000 mL of deionized water, and the phosphorus-doped hierarchical porous carbon prepared above was added in a certain ratio. Ultrasonic dispersion was performed for 30 min, and the mixture was transferred to a reactor and heated at 180 o C for 24 h, the obtained product was washed with deionized water and ethanol, and then dried in vacuum to obtain phosphorus-doped hierarchical porous carbon / MoS2;
[0012] S3, preparation of phosphorus-doped hierarchical porous carbon / MoS2 electrode;
[0013] The phosphorus-doped hierarchical porous carbon / MoS2, conductive additives, and polyvinyl alcohol prepared above were mixed in a mass ratio of 8:1:1, and a small amount of epichlorohydrin was added to mix well, and then coated on a foam titanium substrate and heated at 70 o C and dried in vacuum.
[0014] Furthermore, the method further comprises the following steps:
[0015] S4, preparation of carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode;
[0016] A three-electrode system was used, with phosphorus-doped hierarchical porous carbon / MoS2 electrode as the working electrode, Pt as the counter electrode, and Ag / AgCl electrode as the reference electrode.
[0017] The reaction system contained a certain concentration of aniline, aniline-2-carboxylic acid and 0.1M KClO4. Before the reaction, nitrogen was passed through the reaction system for 30 min to remove oxygen. The polymerization potential was controlled at 1.0 V and the polymerization time was 250 s. After the reaction was completed, a carboxylated conductive polymer film was formed on the surface of the phosphorus-doped hierarchical porous carbon / MoS2 electrode, thereby preparing a carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode.
[0018] The electrochemical polymerization reaction formula for generating carboxylated polyaniline is as follows:
[0019]
[0020] Furthermore, in S1, coal tar is used as a carbon source and phytic acid is used as a phosphorus doping agent to prepare phosphorus-doped hierarchical porous carbon, and a mixture of N2+water vapor+CO2 is used as an activating agent, and the activation time is 2 h.
[0021] Furthermore, in S2, the phosphorus-doped graded porous carbon is added in an amount of 3-9 g.
[0022] Furthermore, in S3, the conductive additive is conductive graphite.
[0023] Furthermore, in S4, the concentrations of aniline and aniline-2-carboxylic acid are the same, both of which are 0.1-0.2 M.
[0024] The beneficial effects of the present invention are as follows: the present invention uses phytic acid with a high phosphorus content as a phosphorus source and F127 as a mesoporous template to prepare phosphorus-doped hierarchical porous carbon, thereby improving the pore structure and hydrophilicity of the carbon material and increasing pseudocapacitance; phosphorus-doped hierarchical porous carbon is composited with MoS2 with high pseudocapacitance to significantly improve the specific capacitance of the electrode material. The carboxylated polyaniline membrane is modified on the surface of the hierarchical porous carbon / MoS2 electrode as an ion exchange membrane by a constant potential method to construct an integrated membrane electrode, which can significantly improve the electrode specific capacitance, hydrophilicity and selective permeability of the ion exchange membrane, thereby improving the desalination performance of MCDI in treating low-concentration uranium-containing wastewater;
[0025] In addition, in step 1 of the present invention, the hierarchical pore carbon is activated by using a mixed gas of N2+water vapor+CO2 (volume ratio 1:1:1), which is conducive to forming a hierarchical pore carbon structure dominated by micropores / mesopores, improving the pore size distribution, and avoiding the problem of easy corrosion of equipment in traditional chemical activation;
[0026] In step 3 of the present invention, the hydrophilic PVA binder is used to replace the traditional hydrophobic binder (such as polyvinylidene fluoride), which can effectively improve the hydrophilicity of the electrode material;
[0027] In step 4 of the present invention, the carboxylated conductive polymer film formed on the surface of the phosphorus-doped hierarchical porous carbon / MoS2 electrode by the constant potential method has good ion exchange performance and conductivity, and can significantly improve the membrane conductivity and ion selective permeability. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION Example 1
[0029] like Figure 1As shown, a method for preparing a carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode comprises the following steps:
[0030] S1. Preparation of phosphorus-doped hierarchical porous carbon
[0031] Coal tar was used as the carbon source to synthesize mesoporous carbon by using the template method: 5% template agent F127 was added to 100 mL coal tar and mixed well, and then 6 g phytic acid (cyclohexanehexol hexaphosphate, molecular formula C6H 18 O 24 P6) as a phosphorus source, and then ultrasonicated for 30 min. The mixed solution was added to the reactor, stirred and reacted at 210 °C for 12 h, and the product was filtered and dried to obtain a phosphorus-doped carbon precursor.
[0032] The phosphorus-doped carbon precursor prepared above was placed in the middle of a tube furnace, heated and carbonized for 2 h at 700 °C in a mixed atmosphere of N2+water vapor+CO2 (volume ratio 1:1:1), and the template F127 was removed simultaneously. The obtained carbonized product was washed with water and vacuum dried to obtain phosphorus-doped hierarchical porous carbon.
[0033] Preparation of S2 and phosphorus-doped hierarchical porous carbon / MoS2
[0034] First, ammonium molybdate (18.6 g) and thiourea (34.2 g) were dissolved in 1000 mL of deionized water, and 3 g of the phosphorus-doped hierarchical porous carbon prepared above was added according to a certain ratio. Ultrasonic dispersion was performed for 30 min, and the mixture was transferred to a reactor and heated at 180 o C for 24 h, and the obtained product was thoroughly washed with deionized water and ethanol and then dried in vacuum to obtain phosphorus-doped hierarchical porous carbon / MoS2.
[0035] S3. Preparation of phosphorus-doped hierarchical porous carbon / MoS2 electrode
[0036] The phosphorus-doped hierarchical porous carbon / MoS2, conductive graphite (conductive additive), and polyvinyl alcohol (PVA aqueous solution, binder) prepared above were mixed in a mass ratio of 8:1:1, and a small amount of epichlorohydrin (ECH cross-linking agent, about 1 wt.% of PVA) was added and mixed thoroughly, coated on a foam titanium substrate (current collector), and heated at 70 o C and dried under vacuum (while cross-linking the PVA).
[0037] S4, Preparation of carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode
[0038] A three-electrode system was used, with phosphorus-doped hierarchical porous carbon / MoS2 electrode as the working electrode, Pt as the counter electrode, and Ag / AgCl electrode as the reference electrode. The reaction system contained 0.15M aniline, 0.15M aniline-2-carboxylic acid, and 0.1M KClO4 (to increase the conductivity of the solution); before the reaction, nitrogen was passed through the reaction system for 30 min to remove oxygen, and the polymerization potential was controlled at 1.0 V and the polymerization time was 250s. After the reaction was completed, a carboxylated conductive polymer film was formed on the surface of the phosphorus-doped hierarchical porous carbon / MoS2 electrode, thereby preparing a carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode.
[0039] The performance of the carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode was tested, showing that its specific capacitance was 142 F / g and its contact angle in aqueous solution was 46 o .
[0040] Among them, the reaction formula for electrochemical polymerization to generate carboxylated polyaniline is as follows:
[0041]
[0042] The above-prepared pair of carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrodes were used as parallel electrodes (electrode active mass 30 mg) for membrane capacitive deionization treatment of 1 L of uranium-containing wastewater with a concentration of 15 mg / L, indicating that the membrane permeation flux was 0.021 m 3 / (m 2 . h), adsorption equilibrium time was 80 min, uranium removal efficiency was 66%, and uranium removal capacity was 330 mg / g. Example 2
[0043] The preparation method of carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode comprises the following steps:
[0044] S1. Preparation of phosphorus-doped hierarchical porous carbon
[0045] Coal tar was used as the carbon source to synthesize mesoporous carbon by using the template method: 5% template agent F127 was added to 100 mL coal tar and mixed well, and then 6 g phytic acid (cyclohexanehexol hexaphosphate, molecular formula C6H 18 O 24 P6) as a phosphorus source, and then ultrasonicated for 30 min. The mixed solution was added to the reactor, stirred and reacted at 210 °C for 12 h, and the product was filtered and dried to obtain a phosphorus-doped carbon precursor.
[0046] The phosphorus-doped carbon precursor prepared above was placed in the middle of a tube furnace, heated and carbonized for 2 h at 700 °C in a mixed atmosphere of N2+water vapor+CO2 (volume ratio 1:1:1), and the template F127 was removed simultaneously. The obtained carbonized product was washed with water and vacuum dried to obtain phosphorus-doped hierarchical porous carbon.
[0047] Preparation of S2 and phosphorus-doped hierarchical porous carbon / MoS2
[0048] First, ammonium molybdate (18.6 g) and thiourea (34.2 g) were dissolved in 1000 mL of deionized water, and 6 g of the phosphorus-doped hierarchical porous carbon prepared above was added according to a certain ratio. Ultrasonic dispersion was performed for 30 min, and the mixture was transferred to a reactor and heated at 180 o C for 24 h, and the obtained product was thoroughly washed with deionized water and ethanol and then dried in vacuum to obtain phosphorus-doped hierarchical porous carbon / MoS2.
[0049] S3. Preparation of phosphorus-doped hierarchical porous carbon / MoS2 electrode
[0050] The phosphorus-doped hierarchical porous carbon / MoS2, conductive graphite (conductive additive), and polyvinyl alcohol (PVA aqueous solution, binder) prepared above were mixed in a mass ratio of 8:1:1, and a small amount of epichlorohydrin (ECH cross-linking agent, about 1 wt.% of PVA) was added and mixed thoroughly, coated on a foam titanium substrate (current collector), and heated at 70 o C and dried under vacuum (while cross-linking the PVA).
[0051] S4, Preparation of carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode
[0052] A three-electrode system was used, with phosphorus-doped hierarchical porous carbon / MoS2 electrode as the working electrode, Pt as the counter electrode, and Ag / AgCl electrode as the reference electrode. The reaction system contained 0.15 M aniline, 0.15 M aniline-2-carboxylic acid, and 0.1 M KClO4 (to increase the conductivity of the solution); before the reaction, nitrogen was passed through the reaction system for 30 min to remove oxygen, and the polymerization potential was controlled at 1.0 V and the polymerization time was 250 s. After the reaction was completed, a carboxylated conductive polymer film was formed on the surface of the phosphorus-doped hierarchical porous carbon / MoS2 electrode, thereby preparing a carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode.
[0053] The performance of the carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode was tested, showing that its specific capacitance was 178 F / g and its contact angle in aqueous solution was 31 o .
[0054] The above-prepared pair of carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrodes were used as parallel electrodes (electrode active mass 30 mg) for membrane capacitive deionization treatment of 1 L of uranium-containing wastewater with a concentration of 15 mg / L, indicating that the membrane permeation flux was 0.023 m 3 / (m 2 . h). The adsorption equilibrium time was 60 min, the uranium removal rate was 95%, and the uranium removal capacity was 476 mg / g. Example 3
[0055] The preparation method of carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode comprises the following steps:
[0056] S1. Preparation of phosphorus-doped hierarchical porous carbon
[0057] Coal tar was used as the carbon source to synthesize mesoporous carbon by using the template method: 5% template agent F127 was added to 100 mL coal tar and mixed well, and then 6 g phytic acid (cyclohexanehexol hexaphosphate, molecular formula C6H 18 O 24 P6) as a phosphorus source, and then ultrasonicated for 30 min. The mixed solution was added to the reactor, stirred and reacted at 210 °C for 12 h, and the product was filtered and dried to obtain a phosphorus-doped carbon precursor.
[0058] The phosphorus-doped carbon precursor prepared above was placed in the middle of a tube furnace, heated and carbonized for 2 h at 700 °C in a mixed atmosphere of N2+water vapor+CO2 (volume ratio 1:1:1), and the template F127 was removed simultaneously. The obtained carbonized product was washed with water and vacuum dried to obtain phosphorus-doped hierarchical porous carbon.
[0059] Preparation of S2 and phosphorus-doped hierarchical porous carbon / MoS2
[0060] First, ammonium molybdate (18.6 g) and thiourea (34.2 g) were dissolved in 1000 mL of deionized water, and 9 g of the phosphorus-doped hierarchical porous carbon prepared above was added according to a certain ratio. Ultrasonic dispersion was performed for 30 min, and the mixture was transferred to a reactor and heated at 180 o C for 24 h, and the obtained product was thoroughly washed with deionized water and ethanol and then dried in vacuum to obtain phosphorus-doped hierarchical porous carbon / MoS2.
[0061] S3. Preparation of phosphorus-doped hierarchical porous carbon / MoS2 electrode
[0062] The phosphorus-doped hierarchical porous carbon / MoS2, conductive graphite (conductive additive), and polyvinyl alcohol (PVA aqueous solution, binder) prepared above were mixed in a mass ratio of 8:1:1, and a small amount of epichlorohydrin (ECH cross-linking agent, about 1 wt.% of PVA) was added and mixed thoroughly, coated on a foam titanium substrate (current collector), and heated at 70o C and dried under vacuum (while cross-linking the PVA).
[0063] S4, Preparation of carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode
[0064] A three-electrode system was used, with phosphorus-doped hierarchical porous carbon / MoS2 electrode as the working electrode, Pt as the counter electrode, and Ag / AgCl electrode as the reference electrode. The reaction system contained 0.15 M aniline, 0.15 M aniline-2-carboxylic acid, and 0.1 M KClO4 (to increase the conductivity of the solution); before the reaction, nitrogen was passed through the reaction system for 30 min to remove oxygen, and the polymerization potential was controlled at 1.0 V and the polymerization time was 250 s. After the reaction was completed, a carboxylated conductive polymer film was formed on the surface of the phosphorus-doped hierarchical porous carbon / MoS2 electrode, thereby preparing a carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode.
[0065] The performance of the carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode was tested, showing that its specific capacitance was 125 F / g and its contact angle in aqueous solution was 48 o .
[0066] The above-prepared pair of carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrodes were used as parallel electrodes (electrode active mass 30 mg) for membrane capacitive deionization treatment of 1 L of uranium-containing wastewater with a concentration of 15 mg / L, indicating that the membrane permeation flux was 0.017 m 3 / (m 2 . h). The adsorption equilibrium time was 90 min, the uranium removal rate was 69%, and the uranium removal capacity was 345 mg / g. Example 4
[0067] The preparation method of carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode comprises the following steps:
[0068] S1. Preparation of phosphorus-doped hierarchical porous carbon
[0069] Coal tar was used as the carbon source to synthesize mesoporous carbon by using the template method: 5% template agent F127 was added to 100 mL coal tar and mixed well, and then 6 g phytic acid (cyclohexanehexol hexaphosphate, molecular formula C6H 18 O 24 P6) as a phosphorus source, and then ultrasonicated for 30 min. The mixed solution was added to the reactor, stirred and reacted at 210 °C for 12 h, and the product was filtered and dried to obtain a phosphorus-doped carbon precursor.
[0070] The phosphorus-doped carbon precursor prepared above was placed in the middle of a tube furnace, heated and carbonized for 2 h at 700 °C in a mixed atmosphere of N2+water vapor+CO2 (volume ratio 1:1:1), and the template F127 was removed simultaneously. The obtained carbonized product was washed with water and vacuum dried to obtain phosphorus-doped hierarchical porous carbon.
[0071] Preparation of S2 and phosphorus-doped hierarchical porous carbon / MoS2
[0072] First, ammonium molybdate (18.6 g) and thiourea (34.2 g) were dissolved in 1000 mL of deionized water, and 6 g of the phosphorus-doped hierarchical porous carbon prepared above was added according to a certain ratio. Ultrasonic dispersion was performed for 30 min, and the mixture was transferred to a reactor and heated at 180 o C for 24 h, and the obtained product was thoroughly washed with deionized water and ethanol and then dried in vacuum to obtain phosphorus-doped hierarchical porous carbon / MoS2.
[0073] S3. Preparation of phosphorus-doped hierarchical porous carbon / MoS2 electrode
[0074] The phosphorus-doped hierarchical porous carbon / MoS2, conductive graphite (conductive additive), and polyvinyl alcohol (PVA aqueous solution, binder) prepared above were mixed in a mass ratio of 8:1:1, and a small amount of epichlorohydrin (ECH cross-linking agent, about 1 wt.% of PVA) was added and mixed thoroughly, coated on a foam titanium substrate (current collector), and heated at 70 o C and dried under vacuum (while cross-linking the PVA).
[0075] S4, Preparation of carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode
[0076] A three-electrode system was used, with phosphorus-doped hierarchical porous carbon / MoS2 electrode as the working electrode, Pt as the counter electrode, and Ag / AgCl electrode as the reference electrode. The reaction system contained 0.10 M aniline, 0.10 M aniline-2-carboxylic acid, and 0.1 M KClO4 (to increase the conductivity of the solution); before the reaction, nitrogen was passed through the reaction system for 30 min to remove oxygen, and the polymerization potential was controlled at 1.0 V and the polymerization time was 250 s. After the reaction was completed, a carboxylated conductive polymer film was formed on the surface of the phosphorus-doped hierarchical porous carbon / MoS2 electrode, thereby preparing a carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode.
[0077] The performance of the carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode was tested, showing that its specific capacitance was 115 F / g and its contact angle in aqueous solution was 49 o .
[0078] The above-prepared pair of carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrodes were used as parallel electrodes (electrode active mass 30 mg) for membrane capacitive deionization treatment of 1 L of uranium-containing wastewater with a concentration of 15 mg / L, indicating that the membrane permeation flux was 0.018 m 3 / (m 2 . h). The adsorption equilibrium time was 90 min, the uranium removal rate was 62%, and the uranium removal capacity was 310 mg / g. Example 5
[0079] The preparation method of carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode comprises the following steps:
[0080] S1. Preparation of phosphorus-doped hierarchical porous carbon
[0081] Coal tar was used as the carbon source to synthesize mesoporous carbon by using the template method: 5% template agent F127 was added to 100 mL coal tar and mixed well, and then 6 g phytic acid (cyclohexanehexol hexaphosphate, molecular formula C6H 18 O 24 P6) as a phosphorus source, and then ultrasonicated for 30 min. The mixed solution was added to the reactor, stirred and reacted at 210 °C for 12 h, and the product was filtered and dried to obtain a phosphorus-doped carbon precursor.
[0082] The phosphorus-doped carbon precursor prepared above was placed in the middle of a tube furnace, heated and carbonized for 2 h at 700 °C in a mixed atmosphere of N2+water vapor+CO2 (volume ratio 1:1:1), and the template F127 was removed simultaneously. The obtained carbonized product was washed with water and vacuum dried to obtain phosphorus-doped hierarchical porous carbon.
[0083] Preparation of S2 and phosphorus-doped hierarchical porous carbon / MoS2
[0084] First, ammonium molybdate (18.6 g) and thiourea (34.2 g) were dissolved in 1000 mL of deionized water, and 6 g of the phosphorus-doped hierarchical porous carbon prepared above was added according to a certain ratio. Ultrasonic dispersion was performed for 30 min, and the mixture was transferred to a reactor and heated at 180 o C for 24 h, and the obtained product was thoroughly washed with deionized water and ethanol and then dried in vacuum to obtain phosphorus-doped hierarchical porous carbon / MoS2.
[0085] S3. Preparation of phosphorus-doped hierarchical porous carbon / MoS2 electrode
[0086] The phosphorus-doped hierarchical porous carbon / MoS2, conductive graphite (conductive additive), and polyvinyl alcohol (PVA aqueous solution, binder) prepared above were mixed in a mass ratio of 8:1:1, and a small amount of epichlorohydrin (ECH cross-linking agent, about 1 wt.% of PVA) was added and mixed thoroughly, coated on a foam titanium substrate (current collector), and heated at 70o C and dried under vacuum (while cross-linking the PVA).
[0087] S4, Preparation of carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode
[0088] A three-electrode system was used, with phosphorus-doped hierarchical porous carbon / MoS2 electrode as the working electrode, Pt as the counter electrode, and Ag / AgCl electrode as the reference electrode. The reaction system contained 0.20 M aniline, 0.20 M aniline-2-carboxylic acid, and 0.1 M KClO4 (to increase the conductivity of the solution); before the reaction, nitrogen was passed through the reaction system for 30 min to remove oxygen, and the polymerization potential was controlled at 1.0 V and the polymerization time was 250 s. After the reaction was completed, a carboxylated conductive polymer film was formed on the surface of the phosphorus-doped hierarchical porous carbon / MoS2 electrode, thereby preparing a carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode.
[0089] The performance of the carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode was tested, showing that its specific capacitance was 131 F / g and its contact angle in aqueous solution was 38 o .
[0090] The above-prepared pair of carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrodes (electrode active mass 30 mg) were used as parallel electrodes for membrane capacitive deionization to treat 1L of uranium-containing wastewater with a concentration of 15 mg / L. The membrane permeation flux was 0.016 m 3 / (m 2 . h). The adsorption equilibrium time was 70 min, the uranium removal rate was 78%, and the uranium removal capacity was 392 mg / g.
[0091] The experimental results of using membrane capacitive deionization (MCDI) to treat 1L of uranium-containing wastewater with a concentration of 15 mg / L in Examples 1 to 5 show that Example 2 (implemented according to the present invention with a phosphorus-doped graded porous carbon addition amount of 6 g in step 2, and an aniline concentration of 0.15 M and an aniline-2-carboxylic acid concentration of 0.15 M in step 4) has the best wastewater treatment effect, at which the membrane permeation flux is 0.023 m 3 / (m 2h). The adsorption equilibrium time was 60 min, the uranium removal rate reached 95%, and the uranium removal capacity was 476 mg / g. With the increase of monomer concentration, the loading amount of carboxylated polyaniline increased, which could improve the electrode specific capacitance, but excessive loading would block the electrode pore structure and make MCDI worse. By adjusting the amount of phosphorus-doped hierarchical porous carbon added and the concentration of polymerized monomers aniline and aniline-2-carboxylic acid, the phosphorus-doped hierarchical porous carbon content and the loading amount of carboxylated polyaniline in the carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode can be optimized, so that the pore structure of phosphorus-doped hierarchical porous carbon matches the pseudocapacitance provided by carboxylated polyaniline, and the synergistic effect of the two is brought into play, thereby optimizing the MCDI desalination performance.
[0092] The present invention uses phytic acid with high phosphorus content as a phosphorus source and F127 as a template to prepare phosphorus-doped hierarchical porous carbon, thereby improving the pore structure and hydrophilicity of the carbon material and increasing pseudocapacitance; phosphorus-doped hierarchical porous carbon is combined with MoS2 with high pseudocapacitance to significantly improve the specific capacitance of the electrode material. The carboxylated polyaniline membrane is modified on the surface of the hierarchical porous carbon / MoS2 electrode as an ion exchange membrane by a constant potential method to construct an integrated membrane electrode, which can significantly improve the electrode specific capacitance, hydrophilicity and selective permeability of the ion exchange membrane, thereby improving the desalination performance of MCDI in treating low-concentration uranium-containing wastewater;
[0093] In addition, in step 1 of the present invention, the hierarchical pore carbon is activated by using a mixed gas of N2+water vapor+CO2 (volume ratio 1:1:1), which is conducive to forming a hierarchical pore carbon structure dominated by micropores / mesopores, improving the pore size distribution, and avoiding the problem of easy corrosion of equipment in traditional chemical activation;
[0094] In step 3 of the present invention, the hydrophilic PVA binder is used to replace the traditional hydrophobic binder (such as polyvinylidene fluoride), which can effectively improve the hydrophilicity of the electrode material;
[0095] In step 4 of the present invention, the carboxylated conductive polymer film formed on the surface of the phosphorus-doped hierarchical porous carbon / MoS2 electrode by the constant potential method has good ion exchange performance and conductivity, and can significantly improve the membrane conductivity and ion selective permeability.
[0096] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode, characterized in that: The steps include: S1. Preparation of phosphorus-doped hierarchical porous carbon Mesoporous carbon was synthesized by using coal tar as the carbon source and template method: 5% template F127 was added to 100 mL coal tar and mixed, and then 6 g phytic acid was added as the phosphorus source and mixed, and ultrasonicated for 30 min. The mixture was added to the reactor and stirred at 210 °C for 12 h. The product was filtered and dried to obtain the phosphorus-doped carbon precursor. The phosphorus-doped carbon precursor prepared above was placed in the middle of a tube furnace, heated and carbonized for 2 h at 700 °C in a mixed atmosphere of N2+water vapor+CO2 in a volume ratio of 1:1:1, and the template F127 was removed simultaneously. The obtained carbonized product was washed with water and vacuum dried to obtain phosphorus-doped hierarchical porous carbon; Preparation of S2 and phosphorus-doped hierarchical porous carbon / MoS2 First, 18.6 g of ammonium molybdate and 34.2 g of thiourea were dissolved in 1000 mL of deionized water, and the phosphorus-doped hierarchical porous carbon prepared above was added in a certain ratio. Ultrasonic dispersion was performed for 30 min, and the mixture was transferred to a reactor and heated at 180 o C for 24 h, the obtained product was washed with deionized water and ethanol, and then dried in vacuum to obtain phosphorus-doped hierarchical porous carbon / MoS2; S3, preparation of phosphorus-doped hierarchical porous carbon / MoS2 electrode; The phosphorus-doped hierarchical porous carbon / MoS2, conductive additives, and polyvinyl alcohol prepared above were mixed in a mass ratio of 8:1:1, and a small amount of epichlorohydrin was added to mix well, coated on a foam titanium substrate, and heated at 70 o C vacuum drying; S4, preparation of carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode; A three-electrode system was used, with phosphorus-doped hierarchical porous carbon / MoS2 electrode as the working electrode, Pt as the counter electrode, and Ag / AgCl electrode as the reference electrode. The reaction system contained a certain concentration of aniline, aniline-2-carboxylic acid and 0.1M KClO4; before the reaction, nitrogen was passed into the reaction system for 30 min to deoxygenate, the polymerization potential was controlled at 1.0 V, and the polymerization time was 250 s. After the reaction was completed, a carboxylated conductive polymer film was formed on the surface of the phosphorus-doped hierarchical porous carbon / MoS2 electrode, thereby preparing a carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode.
2. The method for preparing a carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode according to claim 1, characterized in that: In the S2, the phosphorus-doped graded porous carbon is added in an amount of 3-9 g.
3. The method for preparing a carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode according to claim 1, characterized in that: In S3, the conductive additive is conductive graphite.
4. The method for preparing a carboxylated polyaniline / phosphorus-doped hierarchical porous carbon / MoS2 integrated membrane electrode according to claim 1, characterized in that: In S4, the concentrations of aniline and aniline-2-carboxylic acid are the same, both 0.1-0.2 M.
Citation Information
Patent Citations
Preparation method of polyaniline and molybdenum disulfide intercalated composite material
CN103254429A
Method for self-template and self-doping preparation of supercapacitor phosphorus rich mesoporous carbon
CN108538640A